Working Environment and Well-Being of Nurses in Northern Negros Occidental Hospitals during the COVID-19 Pandemic - Morante, Cyrille; Arnibal, Sheila P. (Technium Social Sciences Journal, 2022)
The study assessed the level of the working environment and extent of the well-being of nurses in northern Negros Occidental Hospitals during the Covid-19 Pandemic. It explored the difference according to the variables, sex, employment status, nursing experience, and hospital affiliation. Lastly, it determined the relationship between the working environment and the well-being of nurses. This study utilized a descriptive, comparative, and correlational design. A stratified random sampling technique was used on 130 nurses from January 2020 to December 2021. Two research instruments were employed and underwent reliability and validity testing before utilization. Results showed the level of quality of the working environment was high (M=3.75, SD=0.77). Among the 5 aspects of well-being, spiritual health was rated to a very great extent (M=3.33, SD=0.59), and understaffing (89.2%) was the top challenge faced by the nurses. The employment status ([t (128) =2.338, p=0.021] showed a significant difference in the extent of the well-being of nurses. Also, there was a relationship between the working environment and the well-being of nurses [p (128) =0.436, p=0.000]. A high-quality working environment and a great extent of well-being signify that nurses render quality services with full compassion despite the challenges they encountered in the workplace.